1995
DOI: 10.1046/j.1471-4159.1995.65010010.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Oligodendrocyte‐ and Myelin‐Specific Genes by a Differential Screening Approach

Abstract: We have isolated several new genes that are specifically expressed by oligodendrocytes in the CNS. This was achieved by differential screening of a rat spinal cord cDNA library with probes derived from normal and from oligodendrocyte‐free spinal cord mRNAs. Four of these genes are exclusively expressed by oligodendrocytes: Three of these are not related to known genes, whereas one encodes the myelin oligodendrocyte glycoprotein (MOG). Four other genes are expressed by oligodendrocytes as well as by Schwann cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 27 publications
2
59
0
Order By: Relevance
“…In normal brain, apolipoprotein D is found primarily in white matter oligodendrocytes (Navarro et al 1998;Ong et al 1999). Finally, in normal younger adults who are continuing to myelinate (Yakovlev and Lecours 1967;Benes et al 1994;Bartzokis et al 2001), brain apolipoprotein D is primarily localized in oligodendrocytes (Schaeren-Wiemers et al 1995;Navarro et al 1998;Kalman et al 2000) as is the case in the rodent CNS where a maturation-associated induction of the gene's expression has been reported (Ong et al 1999).…”
Section: Therapeutic Interventions To Improve Myelinationmentioning
confidence: 94%
See 1 more Smart Citation
“…In normal brain, apolipoprotein D is found primarily in white matter oligodendrocytes (Navarro et al 1998;Ong et al 1999). Finally, in normal younger adults who are continuing to myelinate (Yakovlev and Lecours 1967;Benes et al 1994;Bartzokis et al 2001), brain apolipoprotein D is primarily localized in oligodendrocytes (Schaeren-Wiemers et al 1995;Navarro et al 1998;Kalman et al 2000) as is the case in the rodent CNS where a maturation-associated induction of the gene's expression has been reported (Ong et al 1999).…”
Section: Therapeutic Interventions To Improve Myelinationmentioning
confidence: 94%
“…Glia synthesize, excrete, and express the gene for apolipoprotein D, suggesting a specific role for this molecule in membrane lipid metabolism and repair in the central nervous system (CNS) (Schaeren-Wiemers et al 1995;Kalman et al 2000;Patel et al 1995). Apolipoprotein D levels have been shown to be elevated in old age and in a number of other neuropathologic disorders such as Alzheimer's disease (Kalman et al 2000) and excitotoxic damage (Montpied et al 1999) in regionally specific patterns.…”
Section: Therapeutic Interventions To Improve Myelinationmentioning
confidence: 99%
“…MOBP is a CNS myelinspecific protein that plays a role in stabilizing the myelin sheath (16). Northern blot analysis, in situ hybridization, immunochemistry, and immunoelectron microscopy (16,17) indicated that MOBP is expressed exclusively in CNS white matter and more particularly throughout compact myelin, predominantly at the major dense lines of myelin (16). The encephalitogenic potential of MOBP was demonstrated in H-2 b (18) and H-2 s (19,20) mice, and two separate studies of proliferative response to MOBP peptides (pMOBP) by PBL from MS patients and controls indicated that MOBP65-87 was the region most frequently recognized by MS patients T cells (18).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…Southern blotting analysis confi rmed that these cDNAs were splice variants derived from a single copy of the Mobp gene [3] . During this same period Schaeren-Wiemers et al [4] isolated two clones termed CNS1 and CNS3 which also demonstrated partial sequence identity to the cDNAs described by Yamamoto et al . [3] and to ftg -1.…”
Section: Introductionmentioning
confidence: 89%